Enhancing and creating a community Park Cova Lake of Kota Damansara toward improving natural habitats, landscape ecological and environment as quality of life for healthier ecosystem - Jaafar, Fareez (2018)
Cova Lake is a wetland habitats is in Malaysia are relatively scarce and few attract the number or variety of waterbirds that have been recorded at Kota Damansara, Petaling Jaya. Cova Lake Kota Damansara are located a line between Petaling Jaya and Shah Alam, Selangor. This Cova Lake the potential of community park and urban wetland at Kota Damansara. This study also shows that Cova Lake has the strength of the uniqueness of the wetland through their waterbird habitat and open space. The urban wetland become a product of waterbird environment. Preservation from local communities with this wetland environment will benefit the local economy. The main idea in ecological is to enhancing the Cova Lake of Kota Damansara town, to promote the community park and to reach waterbird habitat benefits.